2023
DOI: 10.3390/su152316469
|View full text |Cite
|
Sign up to set email alerts
|

Plant Diversity in Archaeological Sites and Its Bioindication Values for Nature Conservation: Assessments in the UNESCO Site Etruscan Necropolis of Tarquinia (Italy)

Giulio Zangari,
Flavia Bartoli,
Fernando Lucchese
et al.

Abstract: In archaeological sites, plants can be a risk for monument conservation. However, in these sites, a refugium for plant biodiversity is often detected, such as in the UNESCO site Etruscan necropolis of “Monterozzi” in Tarquinia, which still holds a Special Protection Area for bats. In this site, we previously evaluated the positive and negative effects of vascular plants on the conservation of the hypogeal tombs. To contribute in assessing the role of archaeological sites in supporting plant diversity and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Previous studies on the flora of the Pasargadae site and its interaction with stone monuments revealed the importance of understanding the microhabitat of plant colonization on the remaining structures as a tool for controlling biodeterioration phenomena [17,49]. Additionally, the plant diversity of the site [6] and the distribution of the endemic species with conservation interest emphasized the importance of conservation strategies that consider both the natural and cultural values of the site [5,18,24,33,84]. This is particularly important in the context of plant diversity, as the conservation of these sites can help to ensure the protection of plant diversity [39,85].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies on the flora of the Pasargadae site and its interaction with stone monuments revealed the importance of understanding the microhabitat of plant colonization on the remaining structures as a tool for controlling biodeterioration phenomena [17,49]. Additionally, the plant diversity of the site [6] and the distribution of the endemic species with conservation interest emphasized the importance of conservation strategies that consider both the natural and cultural values of the site [5,18,24,33,84]. This is particularly important in the context of plant diversity, as the conservation of these sites can help to ensure the protection of plant diversity [39,85].…”
Section: Discussionmentioning
confidence: 99%
“…The nomenclature followed the "World of Flora Online" [57]. (11,12,14,29,32), remnants of the Royal Garden watercourses (16)(17)(18), semi-natural grasslands and shrublands under several edaphic conditions (4)(5)(6)(7)10,24,26,28,31,33), and stony and rocky hills (8,9,13,15,(19)(20)(21)(22)27,30).…”
Section: Vegetation Samplingmentioning
confidence: 99%
See 3 more Smart Citations